Towards the Application of Fuzzy Logic for Developing a Novel Indoor Air Quality Index (FIAQI) - Allahbakhsh JAVID; Amir Abbas HAMEDIAN; Hamed GHARIBI; Mohammad Hossein SOWLAT (Iranian Journal of Public Health, 2016)
Background: In the past few decades, Indoor Air Pollution (IAP) has become a primary concern to the point. It is increasingly believed to be of equal or greater importance to human health compared to ambient air. However, due to the lack of comprehensive indices for the integrated assessment of indoor air quality (IAQ), we aimed to develop a novel, Fuzzy-Based Indoor Air Quality Index (FIAQI) to bridge the existing gap in this area.